THE INTERRELATIONSHIP BETWEEN ORAL ARGUMENTATION AND WRITTEN ACADEMIC PERFORMANCE - Abdulhakimova Sarvinoz, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Oral argumentation and written academic performance are closely interconnected components of academic literacy. The ability to construct, articulate, and defend arguments orally plays a significant role in shaping students’ written analytical skills. This article explores the relationship between oral argumentative competence and academic writing achievement in higher education. Drawing on contemporary educational research and discourse theory, the paper examines how structured oral debates, discussions, and presentations enhance students’ critical thinking, coherence, and rhetorical organization in written tasks. The study highlights cognitive, linguistic, and metacognitive processes shared between speaking and writing, demonstrating that strong oral argumentation skills positively influence written academic performance. The article concludes that integrating oral argumentative practices into curricula significantly strengthens students’ academic writing outcomes.